Improving interaction responsiveness of multimedia presentations. (21st July 2008) - Alustwani, Husam; Bahi, Jacques M.; Mostefaoui, Ahmed
The Management of user interactions in distributed multimedia presentations requires addressing new challenging issues. In this paper, we revue the semantic of VCR-like interactions. We argue that using VCR commands in the same way as it is done with video data (accelerating the presentation) is not suitable. Furthermore, those interactions are semantically linked to the content of the presentation; the final objective of users is to quickly browse and access a certain content. Firstly, we define a novel adequate semantic of VCR-like interactions for multimedia presentations. It considers human understanding of accelerated multimedia presentation, as the most important criterion to be taken into account. Secondly, we propose an integrated preloading and replacement strategy, named Content-based Prefetching Strategy (CPS) as a suitable buffer management strategy for those VCR-like functionalities. Finally, we show by multiple series of experimentations that CPS observes minimum response time for VCR-like interactions.